2022
DOI: 10.1186/s12864-022-08891-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crucial lncRNAs and mRNAs in liver regeneration after portal vein ligation through weighted gene correlation network analysis

Abstract: Background Portal vein ligation (PVL)-induced liver hypertrophy increases future liver remnant (FLR) volume and improves resectability of large hepatic carcinoma. However, the molecular mechanism by which PVL facilitates liver hypertrophy remains poorly understood. Methods To gain mechanistic insight, we established a rat PVL model and carried out a comprehensive transcriptome analyses of hepatic lobes preserving portal blood supply at 0, 1, 7, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Using an ischemia-reperfusion 85% hepatectomy mouse model and mRNA microarray analysis, Liu et al [38] performed WGCNA and showed that the changes of hub gene expression were most significant during 6-24 h after hepatectomy. Furthermore, Zhu [39] conducted WGCNA based on a rat portal vein ligation model and transcriptome-wide sequencing and revealed that the changes in hub gene expression were most significant at 0 h after operation. These findings are consistent with and further support our results.…”
Section: Discussionmentioning
confidence: 99%
“…Using an ischemia-reperfusion 85% hepatectomy mouse model and mRNA microarray analysis, Liu et al [38] performed WGCNA and showed that the changes of hub gene expression were most significant during 6-24 h after hepatectomy. Furthermore, Zhu [39] conducted WGCNA based on a rat portal vein ligation model and transcriptome-wide sequencing and revealed that the changes in hub gene expression were most significant at 0 h after operation. These findings are consistent with and further support our results.…”
Section: Discussionmentioning
confidence: 99%